Precursors to self-sustained oscillations in aeroacoustic systems. Issue 3 (April 2016) - Nair, Vineeth; Sujith, RI
In this study, we attempt to provide a repertoire of measures to forewarn the onset of impending flow-induced mechanical oscillations via online health monitoring. To illustrate the principles, the flow of air through a pipe terminated by a circular orifice plate is investigated at various flow velocities using a suitably placed pressure transducer. It is observed that the regimes corresponding to the production of a tone is presaged by operating conditions that display temporarily intermittent bursts of periodic pressure oscillations that emerge from a background of lower-amplitude aperiodic fluctuations. The various model-free measures prescribed in this paper serve as efficient precursors by characterizing these intermittent states, which can potentially arise in aeroacoustic systems when the flow is highly unsteady or turbulent.